THE EFFECT OF THE SOCIO EMOTIONAL APPROACH ON STUDENTS HISTORICAL THINKING SKILLS IN THE SUBJECT OF INDONESIAN NATIONAL MOVEMENT HISTORY IN CLASS XI MAN 2 SERANG CITY: Pengaruh Pendekatan Sosio Emotional Terhadap Keterampilan Berpikir Historis Siswa Pada Materi Sejarah Pergerakan Nasional Indonesia Kelas XI MAN 2 Kota Serang - Nofa Musarofah; Yuni Maryuni; Agus Rustamana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to analyze the effect of the socio-emotional approach on historical thinking skills and describe the improvement in students' social-emotional competence in history learning. The research method used was quantitative with a pre-experimental design in the form of a one group pretest-posttest design. The research sample consisted of 34 students in class XI IPS 2 as the experimental group. Data on historical thinking skills were obtained through tests and analyzed using a t-test, while data on social-emotional competence were collected through questionnaires and analyzed descriptively. The results showed that the socio-emotional approach had a significant effect on students' historical thinking skills with a  significance value of 0,000 < 0,05. In addition, students' social-emotional competencies experienced an increase in average scores from 74,30 on the pretest to 84,45 on the posttest. These findings indicate that the socio-emotional approach is effective when applied in history learning to strengthen students' social-emotional competencies, which in turn can develop students' historical thinking skills.